Analysis of serological data to investigate heterogeneity of malaria transmission: a community-based cross-sectional study in an area conducting elimination in Indonesia - Henry Surendra; Mahardika A. Wijayanti; Elsa H. Murhandarwati; Irnawati; Titik Yuniarti; Mardiati; Herdiana; Maria E. Sumiwi; William A. Hawley; Neil F. Lobo; Jackie Cook; Chris Drakeley; et al. (Malaria Journal, 2019)
Abstract Background Analysis of anti-malarial antibody responses has the potential to improve characterization of the variation in exposure to infection in low transmission settings, where conventional measures, such as entomological estimates and parasitaemia point prevalence become less sensitive and expensive to measure. This study evaluates the use of sero-epidemiological analysis to investigate heterogeneity of transmission in area conducting elimination in Indonesia. Methods Filter paper bloodspots and epidemiological data were collected through a community-based cross-sectional study conducted in two sub-districts in Sabang municipality, Aceh province, Indonesia in 2013. Antibody responses to merozoite surface protein 1 (MSP-119) and apical membrane antigen 1 (AMA-1) for Plasmodium falciparum and Plasmodium vivax were measured using indirect enzyme-linked immunosorbent assay (ELISA). Seroconversion rates (SCR) were estimated by fitting a simple reversible catalytic model to seroprevalence data for each antibody. Spatial analysis was performed using a Normal model (SaTScan v.9.4.2) to identify the clustering of higher values of household antibody responses. Multiple logistic regression was used to investigate factors associated with exposure. Results 1624 samples were collected from 605 households. Seroprevalence to any P. falciparum antigen was higher than to any P. vivax antigen, 6.9% (95% CI 5.8–8.2) vs 2.0% (95% CI 1.4–2.8). SCR estimates suggest that there was a significant change in P. falciparum transmission with no exposure seen in children under 5 years old. Plasmodium falciparum SCR in over 5 years old was 0.008 (95% CI 0.003–0.017) and 0.012 (95% CI 0.005–0.030) in Sukakarya and Sukajaya sub-districts, respectively. Clusters of exposure were detected for both P. falciparum and P. vivax, most of them in Sukajaya sub-district. Higher age, P. vivax seropositivity and use of long-lasting insecticide-treated bed net (LLIN) were associated with higher P. falciparum exposure. Conclusion Analysis of ...